2015
DOI: 10.1073/pnas.1423295112
|View full text |Cite
|
Sign up to set email alerts
|

STIM1 enhances SR Ca 2+ content through binding phospholamban in rat ventricular myocytes

Abstract: In ventricular myocytes, the physiological function of stromal interaction molecule 1 (STIM1), an endo/sarcoplasmic reticulum (ER/SR) Ca2+ sensor, is unclear with respect to its cellular localization, its Ca2+-dependent mobilization, and its action on Ca2+ signaling. Confocal microscopy was used to measure Ca2+ signaling and to track the cellular movement of STIM1 with mCherry and immunofluorescence in freshly isolated adult rat ventricular myocytes and those in short-term primary culture. We found that endoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 51 publications
2
62
1
Order By: Relevance
“…We and others have previously shown that in cardiac myocytes, as well as in smooth muscle cells, STIM1 co-immunoprecipitates with Orai1 and 3 channels under resting conditions 9, 49 . STIM1 might thus represent a large protein complex that can adapt to different stresses to interact with a diversity of complexes 12 . In response to hypertrophic or proliferative stimulus, a large recruitment of Orai3 to STIM1 and Orai1 occurs thus allowing for a store-independent entry 9, 49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have previously shown that in cardiac myocytes, as well as in smooth muscle cells, STIM1 co-immunoprecipitates with Orai1 and 3 channels under resting conditions 9, 49 . STIM1 might thus represent a large protein complex that can adapt to different stresses to interact with a diversity of complexes 12 . In response to hypertrophic or proliferative stimulus, a large recruitment of Orai3 to STIM1 and Orai1 occurs thus allowing for a store-independent entry 9, 49 .…”
Section: Discussionmentioning
confidence: 99%
“…A similar phenomenon has been reported in proliferative smooth muscle cells where STIM1 controls heteromultimers of Orai1 and Orai3 that are regulated by leucotrienes C4 9-11 . Interactions with less Ca 2+ selective channels, such as TRPCs, have also been suggested and STIM1 overexpression leads to dysregulated calcium transients 5, 12 . All together, these data indicate that STIM1 activates in response to stress and can interact with a diversity of plasma membrane channels that will however mediate highly localized Ca 2+ signals.…”
mentioning
confidence: 99%
“…Differentiated EB in low or high glucose conditions were placed on gelatin-coated chamber slides (Lab-Tek, Thermo Fisher Scientific, Waltham, MA, USA) for Ca 2+ imaging based on a previously described protocol [29]. ES-derived cardiomyocytes at day 9 were loaded with 5 μM fluo 4-AM (Thermo Fisher Scientific, Waltham, MA, USA) for 20 minutes at room temperature and replaced with normal Tyrode’s solution containing (in mM) 140 NaCl, 10 Hepes, 0.5 MgCl 2 , 0.33 NaHPO 4 , 5.5 glucose, 1.8 CaCl 2 , and 5 KCl (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…Here, we specifically study the role of the SR protein, Stromal Interaction Molecule 1 (STIM1), and its sarcolemmal partner protein Orai in the development of electrical and contractile remodeling of adult ventricular myocytes after pressure overload. There is some evidence from previous reports that these proteins are present in cardiac myocytes and their abundance increases in disease states 16, 17 . This increase has been linked to maladaptive cardiac hypertrophy 18, 19 .…”
Section: Introductionmentioning
confidence: 98%
“…It is therefore not surprising that a physiological role for STIM and Orai in cardiac myocytes has not been defined. Yet, many independent groups have found STIM1 to be present in cardiac myocytes 27 , though there are conflicting reports on the function of STIM1 and SOCE in these cells 16, 28, 29 . In the diseased heart, SR Ca 2+ regulation is altered 11 and increased SOCE activity has been observed in rodent cardiac disease models.…”
Section: Introductionmentioning
confidence: 99%